Internal Fixation of Long Bone Fractures in Farm Animals - Auer, J. A.; Steiner, A.; Iselin, U.; Lischer, C. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
This study demonstrates that long bone fracture treatment in food and fibre producing animals is in most cases successful. The greatest disadvantage of such treatment are the costs of the surgery and implants.
Keywords: Longbone fractures; cattle; internal fixation